PENINGKATAN HASIL BELAJAR IPA MENGGUNAKAN PENDEKATAN KONSTRUKTIVISME PADA SEKOLAH DASAR NEGERI - Melvanila, Melvanila (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Problem in primary background is in science learning in fourth grade teachers were more likely to use the lecture method and not associate learning with student experience, TOD aims to describe the planning and implementation of science learning in class IV. In this case a constructivist approach of learning is oneapproach that builds students knowledge based on prior knowledgealready possessedstudents through real experience. Using aconstructivist approach to the first cycle of the first meeting of learning outcomes on average 73 and 76 at the second meeting. In the second cycle a very good increase to 82 in the first meeting and 86 in the second meeting. Thus it can be said that a constructivist approach to improve student learning outcomes state primary schools. Kata Kunci : hasil belajar; IPA; pendekatan konstruktivisme